2013
DOI: 10.12688/f1000research.2-189.v2
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Delayed intra-abdominal bleeding following trans-vaginal ultrasonography guided oocyte retrieval for in vitro fertilization in patients at risk for thrombo-embolic events under anticoagulant therapy

Abstract: We report herein, two cases of massive delayed (2 and 4 days) intra abdominal hemorrhage following ovum pick-up (OPU), in patients at risk for thrombo-embolic events, who concomitantly used therapeutic doses of low molecular weight heparin (LMWH). We discuss the possible mechanisms involved in causing the aforementioned delayed bleeding, and call for re-evaluation of the presently accepted anticoagulant co-treatment regimen. These case reports should direct physicians' attention and keep them alert, while cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…To date, 13 case reports or case series studies have reported the need for surgical hemostasis for intraabdominal bleeding after oocyte retrieval, and clinical data were available for 34 patients, including our case [2][3][4][5][13][14][15][16][17][18][19][20][21]. The clinical information in these cases is summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 13 case reports or case series studies have reported the need for surgical hemostasis for intraabdominal bleeding after oocyte retrieval, and clinical data were available for 34 patients, including our case [2][3][4][5][13][14][15][16][17][18][19][20][21]. The clinical information in these cases is summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%